1996
DOI: 10.1021/jo9514331
|View full text |Cite
|
Sign up to set email alerts
|

(1-(Dimethylamino)-2-(diphenylphosphino)ethane)(η3-1-arylallyl)palladium Tetrafluoroborates. Preparation, Isomeric Equilibria, and Correlations of NMR Chemical Shifts with Hammett Substituent Constants

Abstract: 13C NMR differences of chemical shifts (delta(X) - delta(H)) of allyl carbon atoms in a series of trans-(1-(diphenylphosphino)-2-(dimethylamino)ethane)(eta(3)-1-arylallyl)palladium tetrafluoroborates, X ranging from NO(2) to OMe, correlate very well with sigma Hammett constants for C-1 and with sigma(+) for C-3, this carbon atom being in a trans relationship with the positively charged nitrogen atom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…The volatile compounds were then removed from the solution, and (P ʝ N)Pt(Me)Cl (2) remained as a colorless powder in a quantitative yield. 1 [5] with P ʝ N: A solution of [2-(diphenylphosphanyl)ethyl]dimethylamine (P ʝ N) [20] (282 mg, 1.09 mmol) in 10 mL of CH 2 Cl 2 was added slowly to a solution of (nbd)Pt(Me)Cl (365 mg, 1.08 mmol) in 40 mL of CH 2 Cl 2 . After the mixture was stirred for 1 h, the colorless product was filtered and washed with benzene (3 ϫ 5 mL) and pentane (3 ϫ 5 mL).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The volatile compounds were then removed from the solution, and (P ʝ N)Pt(Me)Cl (2) remained as a colorless powder in a quantitative yield. 1 [5] with P ʝ N: A solution of [2-(diphenylphosphanyl)ethyl]dimethylamine (P ʝ N) [20] (282 mg, 1.09 mmol) in 10 mL of CH 2 Cl 2 was added slowly to a solution of (nbd)Pt(Me)Cl (365 mg, 1.08 mmol) in 40 mL of CH 2 Cl 2 . After the mixture was stirred for 1 h, the colorless product was filtered and washed with benzene (3 ϫ 5 mL) and pentane (3 ϫ 5 mL).…”
Section: Methodsmentioning
confidence: 99%
“…The C(9) atom of the ethylene bridge is also disordered. The PtϪC distances of the equatorial methyl substituents [PtϪC(20): Molecular structure of [(κ 2 -P,N)-Ph 2 PCH 2 CH 2 NMe 2 ]-Pt(Me)3 Cl(4)…”
mentioning
confidence: 99%
“…The trend of tuning the endo/exo ratio has been reported mainly for symmetrically disubstituted allyl complexes, while very few papers have mentioned cis/trans control. [17,23,43] All the complexes studied in this paper provide evidence of the influence of the steric bulkiness of the nitrogen substituent on the diastereomeric ratio. Yellow crystals of compound 6 were grown from dichloromethane/pentane.…”
mentioning
confidence: 70%
“…[14,19,35] You et al have observed that, for a complex containing the 2-(phenylthio)-1-(4-tert-butyloxazolinyl)ferrocene ligand, an inversion of the configuration of the oxazoline ring asymmetric carbon slightly affects the endo/exo ratio (3.1:1 vs. 2.1:1), whereas introducing two benzylic groups at the 4-position of the oxazoline ring strongly displaces the equilibrium in favour of the endo diastereomer. [36] The preferential nucleophilic attack at one specific allyl carbon atom is another way to achieve high enantioselectiv- Table 1. 13 C NMR spectroscopic data for allylic carbon atoms in complexes 1 and 2 [14,23,28,37] For complexes 1 and 2, ∆δ lies between 35.7 and 27.2 ppm depending on the isomer (see Table 1). Such a high ∆δ is usual for N,P ligands, given the very different trans influence of the phosphorus and nitrogen atoms, [26] and reveals a higher electrophilicity for the C-1 atom (trans-P) than for the C-3 atom (cis-P; see Scheme 2).…”
Section: Nmr Spectroscopic Studies On Allylic Compounds 1 Andmentioning
confidence: 99%
See 1 more Smart Citation